Education and Income Relationship in Turkey - Ozturk, Feride (The Economics and Finance Letters, 2016)
This paper examines the causal relationship between four different measures of education and income in Turkey using time series data for the period 1971-2013. The four measures are: (a) gross primary-school enrolment, (b) gross secondary-school enrolment, (c) gross higher-school enrolment and (d) government expenditure on education relative to total government expenditure. The analysis employs a Toda and Yamamoto (1995) approach to Granger non-causality. The empirical findings indicate evidence of a unidirectional causality running from secondary-school enrolment to GDP per capita and higher-school enrolment to GDP per capita. The results also indicate that primary education and government spending on education do not Granger cause economic growth and vice versa.